On the Need to Conduct Additional Stress Tests to Evaluate the Safety of the Hydraulic Structures Site at the Zaporizhzhia NPP - Ulyanov, V. Yu.; Bilyk, V. V. (Science and Transport Progress, 2025)
Purpose. Conducting a comprehensive analysis concerning the condition of the cooling pond dam at the Zaporizhzhia Nuclear Power Plant (NPP), which is a key component in the hydraulic structures system at this NPP, to justify further research. Additionally, identifying any extra or previously unaccounted factors that could affect the overall safety of the structure. Methodology. The authors performed a comprehensive review of all available engineering surveys and geotechnical research materials related to the Zaporizhzhia NPP cooling pond dam. These materials were produced by various organizations starting from the completion of the facility in 1985, with particular focus on the period 2011–2018, especially after the publication of the 2011 stress test report. Special attention was given to high-precision geodetic data on settlements and deformations of grades on the cooling pond dam. This enabled a new perspective on the findings of the engineering and geological surveys, as well as the stress tests conducted based on them. Findings. Based on the analysis of the dam body soil research data, previously unaddressed issues were raised and examined, including those related to the facility's operation. The need to conduct new stress tests was justified, considering the current conditions at the NPP site and its surroundings. Practical value. For the first time, a comprehensive analysis of the facility's condition was conducted based on accumulated geotechnical data. The stress tests performed in 2011 were found to be overly optimistic. Originality. The need for further research on the facility was justified, including through a program to evaluate the technical condition of the cooling pond dam using innovative methods from the Prydniprovska State Academy of Civil Engineering and Architecture.